The Utilization of Starfruit Juice and Lemongrass Stems as Antihypertensive Agents in the Banyuurip Village Community, Kedamean Subdistrict, Gresik Regency - Setyawati, Herni; Jaya, Aldi Dwi; Nur, Miranda; Fauziah, Nurul; Mariscal, Farrel (Research and Social Study Institute, 2024)
Hypertension is one of the public health issues requiring special attention, particularly in Banyuurip Village, Kedamean Subdistrict, Gresik Regency. Based on a preliminary survey, it was found that community awareness regarding hypertension management remains low, while the utilization of local herbal remedies has not been optimized. This community service program aims to enhance public understanding of the benefits of starfruit (Averrhoa bilimbi) juice and lemongrass (Cymbopogon citratus) stems as natural antihypertensive agents, as well as to provide training on their processing and usage. The activities were conducted on Thursday, January 18, 2024, targeting the women of the Family Welfare Empowerment (PKK) group. The program included health education, training on the preparation of starfruit juice and lemongrass stems, and monitoring the impact of these herbal remedies on the blood pressure of participating residents. Evaluations were carried out through pre-tests and post-tests to measure participants’ knowledge levels, as well as blood pressure measurements before and after the use of the herbal products. The results showed a significant increase in community understanding of hypertension and the benefits of local herbal remedies. Furthermore, most participants experienced a reduction in blood pressure after regularly consuming the herbal products introduced during the program. This initiative demonstrated that education and training in processing local herbal resources can be an effective strategy for improving public health. The utilization of starfruit and lemongrass as alternative treatments for hypertension is not only cost-effective but also supports community health independence.